Shades of hype. (Economist, 2000)
Reports on the decrease in valuation of stocks of Red Hat and VA Linux, two companies which are focused on the Linux computer operating system. Popularity of the software; Reasons behind the decline in the stock valuation; Success of the two companies, which is a surprise; Other companies which focus on the Linux operating system which is non-proprietary.